Mobility training for the young athlete - Brooks, T.; Cressey, E. (Strength and Conditioning Journal, 2013)
Contemporary corrective exercise techniques emphasizing the importance of adequate movement ability and soft tissue extensibility are now relatively common in most strength and conditioning programs. Despite demonstrated potential for performance deficit, preactivity flexibility training has been employed and continues to be used by many sport coaches. Particularly, in the developing athlete, the differences between mobility and flexibility training are significant. The purpose of this article is to define mobility and discuss the practical implications of incorporating mobility movements, drills, and exercises into programming for young athletes to reduce the risk of injury and maximize performance.